Monolithic transformation : using devops, Agile, and cloud platforms to execute a digital transformation strategy - Coté, Michael (O'Reilly Media, Inc., 2019)
If your company is looking to create new business models through digital transformation, this practical ebook will help get you started. High-powered tech companies and traditional enterprises have dramatically improved business processes through cloud-native technologies and product-centric software techniques, enabling them to react to market changes much faster. Michael Coté from Pivotal explores the strategies and tactics you need to transform your in-house software creation capabilities. Putting the technology in place is relatively easy. The real challenge is changing your organization's culture to take advantage of the technology. Using case studies from enterprises that have suffered through and ultimately benefited from this transformation, this ebook examines the best and worst practices for making the change. You'll learn what it takes to make your company lean, quick, and profitable. With case studies from Duke Energy, Dick's Sporting Goods, the Internal Revenue Service, and Rabobank, this ebook examines the digital transformation process in two parts: Part I: Fostering change --examine the principles of small-batch thinking, user-centric design, and shifting from functional teams to product teams Part II: Cloud-native cookbook for leadership --apply those principles across your organization, from creating and communicating your strategy through building your pipeline and choosing the right cloud platform.